# Extensions 1→N→G→Q→1 with N=C32×M4(2) and Q=C2

Direct product G=N×Q with N=C32×M4(2) and Q=C2
dρLabelID
M4(2)×C3×C6144M4(2)xC3xC6288,827

Semidirect products G=N:Q with N=C32×M4(2) and Q=C2
extensionφ:Q→Out NdρLabelID
(C32×M4(2))⋊1C2 = C3×C8⋊D6φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)):1C2288,679
(C32×M4(2))⋊2C2 = C3×C8.D6φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)):2C2288,680
(C32×M4(2))⋊3C2 = C243D6φ: C2/C1C2 ⊆ Out C32×M4(2)72(C3^2xM4(2)):3C2288,765
(C32×M4(2))⋊4C2 = C24.5D6φ: C2/C1C2 ⊆ Out C32×M4(2)144(C3^2xM4(2)):4C2288,766
(C32×M4(2))⋊5C2 = C32×C8⋊C22φ: C2/C1C2 ⊆ Out C32×M4(2)72(C3^2xM4(2)):5C2288,833
(C32×M4(2))⋊6C2 = C32×C8.C22φ: C2/C1C2 ⊆ Out C32×M4(2)144(C3^2xM4(2)):6C2288,834
(C32×M4(2))⋊7C2 = C3×S3×M4(2)φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)):7C2288,677
(C32×M4(2))⋊8C2 = C3×D12.C4φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)):8C2288,678
(C32×M4(2))⋊9C2 = M4(2)×C3⋊S3φ: C2/C1C2 ⊆ Out C32×M4(2)72(C3^2xM4(2)):9C2288,763
(C32×M4(2))⋊10C2 = C24.47D6φ: C2/C1C2 ⊆ Out C32×M4(2)144(C3^2xM4(2)):10C2288,764
(C32×M4(2))⋊11C2 = C3×C12.46D4φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)):11C2288,257
(C32×M4(2))⋊12C2 = C3×D12⋊C4φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)):12C2288,259
(C32×M4(2))⋊13C2 = C12.19D12φ: C2/C1C2 ⊆ Out C32×M4(2)72(C3^2xM4(2)):13C2288,298
(C32×M4(2))⋊14C2 = C62.37D4φ: C2/C1C2 ⊆ Out C32×M4(2)72(C3^2xM4(2)):14C2288,300
(C32×M4(2))⋊15C2 = C32×C4.D4φ: C2/C1C2 ⊆ Out C32×M4(2)72(C3^2xM4(2)):15C2288,318
(C32×M4(2))⋊16C2 = C32×C4≀C2φ: C2/C1C2 ⊆ Out C32×M4(2)72(C3^2xM4(2)):16C2288,322
(C32×M4(2))⋊17C2 = C32×C8○D4φ: trivial image144(C3^2xM4(2)):17C2288,828

Non-split extensions G=N.Q with N=C32×M4(2) and Q=C2
extensionφ:Q→Out NdρLabelID
(C32×M4(2)).1C2 = C3×C12.53D4φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)).1C2288,256
(C32×M4(2)).2C2 = C3×C12.47D4φ: C2/C1C2 ⊆ Out C32×M4(2)484(C3^2xM4(2)).2C2288,258
(C32×M4(2)).3C2 = C62.8Q8φ: C2/C1C2 ⊆ Out C32×M4(2)144(C3^2xM4(2)).3C2288,297
(C32×M4(2)).4C2 = C12.20D12φ: C2/C1C2 ⊆ Out C32×M4(2)144(C3^2xM4(2)).4C2288,299
(C32×M4(2)).5C2 = C32×C4.10D4φ: C2/C1C2 ⊆ Out C32×M4(2)144(C3^2xM4(2)).5C2288,319
(C32×M4(2)).6C2 = C32×C8.C4φ: C2/C1C2 ⊆ Out C32×M4(2)144(C3^2xM4(2)).6C2288,326

׿
×
𝔽